Cognitive Behavioural Guided Therapy of Obsessive‑Compulsive Symptomatology in a Boy with Autism: Case Study - Lenka Vacková (Listy klinicke logopedie)
The case report focuses on Cognitive Behavioural Guided Therapy of obsessive‑compulsive symptomatology in a boy with autism and other neurodevelopmental disorders in comorbidity. It describes the complex clinical picture of the disorder and long‑term therapy.